Menguji Efektivitas Vaksinasi Covid-19 di Indonesia - Dedi Junaedi; Muhammad Rizal Arsyad; Faisal Salistia; Moh. Romli (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to analyze the effectiveness of vaccinations and policies to overcome the Covid-19 pandemic in Indonesia. The quantitative analysis method with a dummy variable multiple regression approach was used to examine the vaccination times series data, cases, death and recovery of Covid-19 patients for the period December 2020 – August 2021. The results show vaccination (especially dose 2) and the PPKM policy (Enforcement of Restrictions on Community Activities). have a significant impact on increasing cases, deaths and recoveries of Covid-19. The impact on recovery is relatively higher than the impact on additional cases and deaths. A similar trend occurs when considering the impact of PPKM policies (micro, emergency and levels 1-4) on the increase in recovery, which is relatively higher than the similar impact on the rate of increase in cases and deaths. The impact on increasing cases and deaths can be said to be a risk that needs to be considered in future policy implementation.